Social networks and gamification as transformative communication tools: Tourism and the pandemic - Lavilla, David; Ayestarán Crespo, Raquel (Street Art & Urban Creativity, 2025)
The pandemic, particularly during the period of confinement, has marked a turning point in digital transformation across nearly all areas of business and knowledge. The tourism sector serves as a prime example. Although in-person visits to emblematic locations in each country were not possible, new avenues have opened up to bring the world of tourism and the prosumer closer together (Toffler, 1980). Gamification (Teixes, 2014) has played a decisive role in this process. Through apps and virtual and immersive communication techniques, the connected user has been able to discover information about many of the places they have longed to visit in a tangible way. Therefore, it could be argued that tourist destinations themselves have recognised technology as a tool to enhance engagement with their future visitors.